Analisis Workabilitas dan Kuat Tekan Beton dengan Campuran Limbah Keramik sebagai Material Alternatif - Sudarso Sudarso (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
The rapid expansion of construction activities has led to increased concrete consumption, resulting in excessive exploitation of natural aggregate resources and growing environmental concerns. To mitigate this issue, ceramic waste has been investigated as an alternative material in concrete production. This study examines the effect of ceramic waste powder used as a filler on the workability and compressive strength of concrete. Ceramic waste powder was applied as a partial replacement for fine aggregate at proportions of 0%, 15%, 25%, 35%, and 45%. The concrete mixtures were produced using Ordinary Portland Cement Type I, natural sand, crushed stone as coarse aggregate, and potable water, all conforming to Indonesian National Standards (SNI). Workability was assessed through slump tests in accordance with SNI 1972:2008, while compressive strength tests were performed on cylindrical specimens at 28 days following SNI 1974:2011. The compressive strength for each mixture was determined from the average of three specimens. The results show that increasing ceramic waste content slightly reduced slump values, from 17.20 cm in the control mix to 16.60 cm at 45% replacement, although all mixtures met the required workability standards. A gradual decrease in compressive strength was also observed, from 17.79 MPa to 16.65 MPa at the highest replacement level. However, this reduction was not significant, indicating that ceramic waste powder can be used in normal-strength concrete without substantially affecting performance. The utilization of ceramic waste therefore represents a sustainable alternative to reduce natural aggregate consumption while maintaining acceptable concrete properties.